Enhancing the growth and essential oil components of Lavandula latifolia using Malva parviflora extract and humic acid as biostimulants in a field experiment - Mervat El-Hefny; Mahmoud Khattab Hussien (Scientific Reports)
Abstract Natural extracts as biostimulants have the potential to enhance the productivity and growth of many medicinal and aromatic plants. This study aimed to enhance the growth, and essential oil (EO) content, as well as composition of Lavandula latifolia Medik. by using Malva parviflora L. extract (ME) as a biostimulant in combination with humic acid (HA) in a field experiment in two successive seasons of 2022 and 2023. The phenolic, flavonoid and water-soluble vitamins of the ME were analyzed using an HPLC. The protein amino acids of the ME were identified by an amino acid analyzer. The prepared concentrations of HA (0, 1, 2, and 4 g/L) were applied to the soil. While, they for ME (0, 2, 4, and 6 g/L) were added as a foliar spray. The EO compositions collected from the leaves of the treated L. latifolia plants were subjected to the hydro-distillation method and analyzed using GC-MS. The most prevalent vitamins found in ME were vitamin B12, vitamin C, and folic acid. Besides, several phenolic compounds were found in ME, such as catechol, cinnamic acid and syringic acid, while flavonoid chemicals, such as luteolin and quercetin. Also, alanine, ammonia, aspartic acid, glutamic acid, glycine, and tyrosine were the ME’s most prominent nitrogenous and amino acid components. The most effective treatments of HA and ME on the plant height, the number of branches/plant, and plant fresh weight were 4 + 6 g/L and 4 + 2 g/L for leaf area and chlorophyll content, it was 4 + 4 g/L; and for EO percentage were 4 + 0 g/L, 2 + 0 g/L, and 4 + 4 g/L, compared to the control treatment for each characteristic. The main EO compounds eucalyptol, camphor, α-pinene, β-pinene, Δ-elemene, germacrene D-4-ol, isoborneol, β-caryophyllene oxide, and tau.-cadinol identified in the leaves were found in the range of 28.74–46.19%, 15.34–30.49%, 3.39–7.16%, 0–5.08%, 0–5.18%, 0–3.20%, 0–3.31% and 0–3.40%, respectively. It can be concluded that a combination treatment of HA and ME as natural biostimulant compounds at 4 + 4 g/L could be recommended for good plant growth, and EO quantity of L. latifolia plants.